EP1094 Quality of life assessment in gynae-onco survivors. (1st November 2019) - Bahadur, A; Vdovichenko, N; Mundhra, R; Chawla, L; Yadav, A; Kumari, P; Kumari, S; Bhattacharya, N; Kashibhatla, J; Das, D; Prateek, S; Chaturvedi, J
Abstract : Introduction/Background: Quality of life (QOL) is of vital concern to cancer survivors, their families and care providers. Patients' go through emotional distress, altered life priorities, & fear of unknown. Primary objective of this study was to compare quality of life of disease-free patients after therapy for gynecologic malignancies. We assessed difference between emotional, physical, spiritual, social/family, functional well-being, financial burden, treatment satisfaction with QOL score according to FACIT. Methodology: This cross sectional study was conducted in Gynaeoncology OPD at AIIMS, Rishikesh over a period of ten months from March 2018 to December 2018. Participants completed self-report assessments of psychosocial, spiritual, and physical well-being, including social support, optimism, hopelessness, depressive and anxious symptoms. Patients were asked to consider how they felt in the previous 7 days. Results: 60 patients with a mean age of 44.3 years (32–69) were evaluated. Among malignant we found of 52.3% had endometrial cancer, 14.2% each had ovarian, cervical and vulval cancer and 5% breast cancer. 70% patients did not go to hospital despite being symptomatic. 45% were not aware that these symptoms needed evaluation, 25% stated hospital was far away, 20% had financial constraints, 10% Scared of cancer diagnosis. The mean FACIT score in malignant group was 39.5 (32.5–58.6), lowest score observed in cervical cancer. Higher levels of optimism were significantly associated with fewer anxious and depressive symptoms, less hopelessness, and better QOL. Higher levels of perceived social support were also significantly associated with better QOL Conclusion: Optimism and social support serve as protective factors against distress in gynae malignancy survivors. QOL of cancer survivors requires comprehensive care & is best described from patients' perspective. Future clinical research must focus on interventions that attend to patients´ expectations for positive experiences and in expansion of social support. Disclosure: Nothing to disclose